Reviewing the Challenge and Practices of Human Factor Involvement in Requirement Specification Validation - Fauziah, Zainuddin; Ruzaini, Abdullah Arshah; Rozlina, Mohamed (American Scientific Publisher, 2018)
Software requirement specification or documentation is the expected main output from requirement engineering process that specify the agreed requirements at appropriate level of detail; this document is expected to be understandable by both the development team and system stakeholders. The purpose of this study is to identify and analyze existing human involvement in requirement specification validation studies according to the formulated research question. Relevant keywords were used for the search term in various type of journal articles, conference papers, workshop, book chapters and IEEE bulletins; to identify main study on the related human factor and requirement specification validation. 39 primary studies were selected from the systematic literature review. The review identified current trend of human factor involvement in specification validation and the most widely used techniques for validation purpose. The finding suggest human factor involvement in this area are still relevant yet need more focus on specification presented informally (natural language) and visual form is the most popular kind of presentation in assisting human factor in this issue.